A duopoly game model for pricing and green technology selection under cap-and-trade scheme. (March 2021) - Pan, Yanchun; Hussain, Jafar; Liang, Xingying; Ma, Jianhua
Highlights: Pricing behavior has been investigated based on the implementation of green technology in the duopoly market. The study was analyzed by using simulation modeling and optimization. Optimum product price was found to maximize profit under green technology implementation. Subsidy policies from government has been extracted to maximize profit of generating company and to keep the environment clean. Abstract: To implement green technology (GT) in the operational decisions of pollution generating companies, carbon emissions is the major constraint that needs to be considered under a cap-and-trade (C&T) scheme. Due to carbon emissions, GT needs to be considered based on optimal pricing decisions. In this paper, a two-party (one greener and one dirtier manufacturer) game model considering green consumption preferences is proposed. To achieve the desired results, simulation-based gaming was used and a conceptual model was developed to verify functions. Simulation experiments were designed by changing GT costs and carbon prices. The study discovered that whether greener or dirtier manufacturers implement GT depends on various scenarios of cost and carbon emissions reduction of GT and carbon emissions for producing per unit of product. As the GT cost increases, the chance of GT implementation by both manufacturers decreases. When the carbon price is too low, neither manufacturer will implement GT since it is cheaper to directly purchase emissions permits from the trading market. However, when the carbon price is sufficiently high, both resort to GT to reduce carbon emissions due to the high emissions costs. This issue is resolved by providing subsidies based on the emissions reduction rate to both manufacturers. The government adopted this policy because it leads to greater emissions reduction. We provide a higher subsidy rate to Manufacturer 2 (M2) than Manufacturer 1 (M1) because Manufacturer 2 is greener than Manufacturer 1. After receiving the 3.481996 renminbi (RMB) subsidy, Manufacturer 1 is capable of implementing GT and its optimum product price increases from 3.648808 RMB to 4.936556 RMB. When we provide a 3.6 RMB subsidy to M2, then it is able to implement GT, although its product price increases slightly from 7.921875 RMB to 7.990234 RMB because it bears higher unit production costs to maintain equilibrium and must therefore charge a higher product price.